ANALISIS KAWASAN LONGSOR MENGGUNAKAN PEMROGRAMAN R DI KECAMATAN AKABILURU KABUPATEN LIMAPULUH KOTA - Isra Haryati Diva; Iswandi Umar (JURNAL BUANA, 2022)
The purpose of research is (1) to determine the location of the occurrence of landslides in 2016-2021. (2) knowing the dominant factor of landslide using R programming. (3) knowing the landslide susceptibility area in Akabiluru District. The variables used are the point of occurrence of landslides, slope, slope direction, source rock, soil type, rainfall, land use, vegetation density and landform. The landslide point is divided into 50% test data and 50% train data. The method used is bivariate statistics assisted by the R programming language. The results of the study are that there are 30 points of landslide occurrence from 2016-2021 which are spread in Akabiluru District. Factors dominant the occurrence of landslides are slope with AUC 0.78, land use with AUC 0.72, source rock with AUC 0.69, landforms with AUC 0.68, aspect with AUC 0.71, soil type with AUC 0.65. From the total WoE calculation, the AUC value is 0.75 and produces a map of the landslide susceptibility zone which consists of 4 classes, namely high class (20.84%), middle class (26.35%), low class (25.74%) and very low class (27.07% ).